2008
DOI: 10.4049/jimmunol.181.4.2813
|View full text |Cite
|
Sign up to set email alerts
|

Annexin-1 Mediates TNF-α-Stimulated Matrix Metalloproteinase Secretion from Rheumatoid Arthritis Synovial Fibroblasts

Abstract: Annexins are intracellular molecules implicated in the down-regulation of inflammation. Recently, annexin-1 has also been identified as a secreted molecule, suggesting it may have more complex effects on inflammation than previously appreciated. We studied the role of annexin-1 in mediating MMP-1 secretion from rheumatoid arthritis (RA) synovial fibroblasts (SF) stimulated with TNF-α. TNF-α induced a biphasic secretion of annexin-1 from RA SF. Early (≤60 min), cycloheximide-independent secretion from preformed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 49 publications
1
37
1
2
Order By: Relevance
“…LXA 4 inhibited IL1b-induced MMP3 synthesis in synovial fibroblasts with concurrent up-regulation of the counter-regulatory molecules tissue inhibitor of metalloproteinase-1 and -2 (Sodin-Semrl et al 2000). However, ANXA1 was shown to stimulate secretion of MMP1 in the same cell type suggesting that individual mediators might have functionally distinct roles in tissue remodelling (Tagoe et al 2008).…”
Section: Resolution Mediator Downstream Effector Functionsmentioning
confidence: 99%
“…LXA 4 inhibited IL1b-induced MMP3 synthesis in synovial fibroblasts with concurrent up-regulation of the counter-regulatory molecules tissue inhibitor of metalloproteinase-1 and -2 (Sodin-Semrl et al 2000). However, ANXA1 was shown to stimulate secretion of MMP1 in the same cell type suggesting that individual mediators might have functionally distinct roles in tissue remodelling (Tagoe et al 2008).…”
Section: Resolution Mediator Downstream Effector Functionsmentioning
confidence: 99%
“…[39][40][41][42][43] Real-time PCR analysis of cultured human cartilage explants show that both TNF and IL-1β strongly induce ADAMTS-7 and ADAMTS-12 expression. 44 Interestingly, this induction does not occur for ADAMTS-12 in human fetal fibroblasts, suggesting that there may be some tissue specificity for this effect.…”
Section: Dovepressmentioning
confidence: 99%
“…30 Studies of the MAPK cascades activated during positive and negative selection have indicated that positively selected ligands induce a slow and sustained accumulation of Erk activity; in contrast, ligands that induce negative selection provoke a strong and transient burst of Erk phosphorylation. [31][32][33][34] Here we show that stimulation of AnxA1 -/-thymocytes with anti-CD3 caused a delayed and weaker phosphorylation of Erk1/2 compared to their NFκB than CD4 SP cells; and, furthermore, activation of this transcription factor determines the threshold of signalling responsible for positive and negative selection of MHC class I-restricted CD8 cells.…”
mentioning
confidence: 99%